PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KEPUASAN KERJA PEGAWAI DAN DAMPAKNYA TERHADAP KINERJA PEGAWAI PADA BADAN NARKOTIKA NASIONAL PROVINSI JAMBI - Heleicia, Kiki (JUMANJI (JURNAL MANAJEMEN JAMBI), 2023)
The purpose of this study was to describe the motivation, discipline, job satisfaction and performance at the Kantor Badan Narkotika Nasional (BNN) Provinsi Jambi, knowing and analyzing the influence between motivation and discipline directly and indirectly on employee job satisfaction at the Kantor BNN Provinsi Jambi, knowing and analyzing the influence between motivation and discipline directly and indirectly on the performance of employees at the Kantor BNN Provinsi Jambi, knowing and analyzing the influence between performance and job satisfaction on the BNN of Jambi Province and knowing and analyzing the influence between motivation and discipline on performance through job satisfaction at the Kantor BNN Provinsi Jambi. The population of this study is all employees of the Kantor BNN Provinsi Jambi as many as 68 people. The population has a close relationship with the problems studied. Samples are part of the population elements to be studied. In this study used probability sampling technique because the population in this study is not very large. Motivation and Discipline directly and indirectly have a positive influence on the performance of employees at the Office of the Kantor BNN Provinsi Jambi. Job satisfaction has a direct influence on employee performance at the Office of the BNN of Jambi Province. Motivation and Discipline through job satisfaction can have a direct and indirect effect on performance., the influence of orgnaisasi commitment to job satisfaction through performance and directly Motivation and Discipline through performance to job satisfaction